Urine complement analysis implies complement activation is involved in membranous nephropathy - Xu, Yingxue; Li, Yi; Zhang, Yong; Li, Guisen (Frontiers in Medicine, 2025)
BackgroundThe onset and progression of membranous nephropathy (MN) have been associated with complement activation, yet the overall characteristics of this activation in the kidneys remain unclear. In our study, we utilized urine proteomic data to investigate the features of complement activation. We examined the relationship between urine complement components and both clinicopathological features and clinical outcomes in patients with MN.MethodsDifferential expression proteins (DEPs) analysis was performed using proteomic data from urine samples collected from 50 patients with MN, 50 patients with IgA nephropathies (IgAN), and 72 healthy controls (HC). Then, Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analyses were carried out on the DEPs identified in MN. We further investigated the differentially expressed urinary complement proteins in MN patients, exploring their relationships with clinicopathological features and clinical remission. Next, 11 representative complements were selected for validation. Immunohistochemistry and immunofluorescence techniques were employed to compare the expression of CD59 and C5b-9 in renal tissues from MN patients, with analyses conducted on both the clinical remission group and the no remission group (n = 6 in each group).ResultsTotal 1,427 differentially expressed proteins were identified between the MN and HC groups. KEGG pathway analysis showed significant enrichment of these DEPs in the complement-activated pathway within the MN group. Additionally, a correlation was found between proteinuria and the levels of 27 urinary complement proteins. Notably, Collectin12 (collec12) and C1s were positively correlated with tubular atrophy/interstitial fibrosis (TIF) and monocyte infiltration. Furthermore, urine CD59 emerged as a predictor of clinical remission. Lower deposition of C5b-9 in renal tissue and higher expression of CD59 were detected in clinical remission group than non-remission group.ConclusionIn patients with MN, abnormal levels of complement components in urine are commonly observed. Currently, the use of complement inhibitors has brought new hope for the treatment of MN. The factor B inhibitor LNP023 and the factor D inhibitor BCX9930 are undergoing clinical trials for the treatment of MN. Our study indicates that complement abnormalities could serve as clinical biomarkers for tracking the progression of MN, predicting clinical remission, and guiding targeted complement therapy for those affected.